Protein Electrostatic Properties Predefining the Level of Surface Hydrophobicity Change upon Phosphorylation - Polyansky, Anton A. (American Chemical Society, 2012)
[Image: see text] We use explicit-solvent, molecular dynamics simulations to study the change in polar properties of a solvent-accessible surface for proteins undergoing phosphorylation. We analyze eight different pairs of proteins representing different structural classes in native and phosphorylated states and estimate the polarity of their surface using the molecular hydrophobicity potential approach. Whereas the phosphorylation-induced hydrophobicity change in the vicinity of phosphosites does not vary strongly among the studied proteins, the equivalent change for complete proteins covers a surprisingly wide range of effects including even an increase in the overall hydrophobicity in some cases. Importantly, the observed changes are strongly related to electrostatic properties of proteins, such as the net charge per residue, the distribution of charged side-chain contacts, and the isoelectric point. These features predefine the level of surface hydrophobicity change upon phosphorylation and may thus contribute to the phosphorylation-induced alteration of the interactions between a protein and its environment.